2001
DOI: 10.1093/rheumatology/40.5.499
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among bone mineral densities, static alignment and dynamic load in patients with medial compartment knee osteoarthritis

Abstract: Our results suggest that the bone mineral distribution of the proximal tibia is directly affected but lumbar BMD is not influenced by the local mechanical stress around the knee with medial compartment OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
126
3
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(150 citation statements)
references
References 37 publications
18
126
3
3
Order By: Relevance
“…This finding is consistent with some DXA studies (14), but not others, in which both increased and decreased aBMD have been reported in those with knee OA (15)(16)(17). However, it is difficult to make direct comparisons given the differences between DXA and pQCT.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This finding is consistent with some DXA studies (14), but not others, in which both increased and decreased aBMD have been reported in those with knee OA (15)(16)(17). However, it is difficult to make direct comparisons given the differences between DXA and pQCT.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, the medial knee joint compartment experiences greater load than the lateral compartment (27). This load differential is exacerbated by more severe disease (28) and joint malalignment (17,29). However, within the medial compartment, the actual distribution of loading and cartilage wear patterns across the tibial plateau are complex, heterogeneous, and not consistently established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some previous studies have found similar strengths of correlation as found in the present study between dynamic loading parameters and BMD or BMC [5,11,36], these studies have focused on populations with gait abnormalities due to knee and hip osteoarthritis or total hip arthroplasty. The present study focused on normal subjects with no known musculoskeletal problems.…”
Section: Discussionsupporting
confidence: 57%